Quadrupole lens with the controlled sextupole component - Mytsykov, A.O.; Rezaev, A.V.; Muratov, V.I. (Вопросы атомной науки и техники, 2001)
In the paper the quadrupole lens with a controlled sextupole component is considered. The results of magnetic field modeling for various modes of operations of a lens are shown. The required field is realized with the help of the special pole shape and by the additional excitation windings. The lens described is supposed to be used in the compact cyclic accelerators, sources of synchrotron and X-ray radiation.